Antibacterial, Antioxidant, and Raw 264.7 Cell Line Proliferative Effect of 5-[(4-Nitro- Benzylidene)-Amino]-2H-Pyrazol-3-ol - Joseph, Dr. Okoli Bamidele (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Pyrazole derivatives are considered important scaffolds that possess cocktails of pharmacological activities. However, no study has assessed their effects on the proliferation of macrophages. Aim: In this study, 4-nitrophenyl derivative (HL1) containing the 1H-pyrazol-5-ol moiety was synthesized, characterized, and assessed for antibacterial as well as cell proliferative effects. Materials and Methods: HL1 was characterized using an elemental analyzer, thermogravimetric analysis, X-ray diffraction, and various spectrophotometric methods. The antibacterial effect of HL1 on three Gram-positive bacterial strains, namely Enterococcus faecalis, Staphylococcus aureus, and Staphylococcus epidermidis, and three Gram-negative bacterial strains, namely Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa, was determined using the minimal inhibition assays. The RAW 267.4 macrophage cell line was used to assess the effect of HL1 on mitochondrial activity using the CellTiter® blue cell viability assay. Results: The thermogram and diffractogram plots registered thermal stability slightly above the melting point of HL1 and a crystal size of 13.01 nm, respectively. The characterization studies indicated the presence of azomethine moiety at 1701.65 cm−1, δH 9.13, and δC 156.85 ppm on the Fourier-transform infrared,1H, and 13C nuclear magnetic resonance, respectively. The synthesized pyrazole moiety exhibited significant antioxidant activity (IC50 ≤ 0.41 ± 0.02 μM) compared to the acid controls (IC50 ≤ 0.58 ± 0.01 μM) and preserved pharmacological integrity at high temperature but was found not to have any antibacterial effects. Conclusion: The effect of HL1 on the Raw 267.4 cell line intimated a significant increase in the mitochondrial function of the macrophage cells (12.5 μg/ml [127 ± 3 %; P < 0.0007] vs. control) indicating an increase in cell proliferation.